2021
DOI: 10.1016/j.jinf.2021.07.036
|View full text |Cite
|
Sign up to set email alerts
|

CCL1 and IL-2Ra differentiate Tuberculosis disease from latent infection Irrespective of HIV infection in low TB burden countries

Abstract: Objectives: To evaluate the performance of selected host immunological biomarkers in differentiating tuberculosis (TB) disease from latent TB infection (LTBI) in HIV uninfected and infected individuals enrolled in TB low-burden countries. Design: Participants with TB disease ( N = 85) and LTBI ( N = 150) were recruited from prospective cohorts at hospitals in Norway and Denmark. Plasma concentrations of 54 host markers were assessed by Luminex multiplex immunoassays. Using receiver operator characteristic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…We show that PTB in HIV-infected patients is characterized by increased systemic inflammation compared to LTBI persons. This is in accordance with previous reports showing elevated inflammatory markers (such as CRP, IP-10, IFN-γ, CCL1, and VEGF) in unstimulated plasma or serum in aTB compared to LTBI or other respiratory diseases regardless of HIV status [15,16,18]. In HIV negative individuals, distinct inflammatory profiles in PTB versus extra pulmonary TB have been reported, which were speculated to be the consequence of differences between disseminated versus more localized infection [40].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We show that PTB in HIV-infected patients is characterized by increased systemic inflammation compared to LTBI persons. This is in accordance with previous reports showing elevated inflammatory markers (such as CRP, IP-10, IFN-γ, CCL1, and VEGF) in unstimulated plasma or serum in aTB compared to LTBI or other respiratory diseases regardless of HIV status [15,16,18]. In HIV negative individuals, distinct inflammatory profiles in PTB versus extra pulmonary TB have been reported, which were speculated to be the consequence of differences between disseminated versus more localized infection [40].…”
Section: Discussionsupporting
confidence: 93%
“…We assessed the performance of previously described soluble biosignatures our data set to and compared soluble biosignature performance to HLA-DR expression. We identified six different published biosignatures which include analytes measured in this study: [IL-12p40 + IL-10] [21], [IFN-γ + IL-10 + IL-12p40] [21], [TNF-α + IL-12p40] [21], [CCL1 + CRP] [15], [CCL1 + TNF-α] [16], and [IL-6Rα + IL-2Rα] [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2R gene polymorphism analysis including variants of IL-2RA, IL-2RB, and IL-2RG revealed that only IL-2RA gene polymorphisms showed a statistically significant association with susceptibility to TB [50]. In the study involving 235 participants with TB and latent Mtb infection, serum levels of IL-2Ra and chemokine CCL1 were higher in TB compared to latently infected individuals; therefore, they can be used as a diagnostic tool to discriminate between these groups [51]. IL-2R appears to have the potential to be used in the therapy of both TB and melanoma by binding fusion toxin composed of the catalytic and transmembrane domains of diphtheria toxin fused to human IL-2, leading to selective depletion of cells expressing the high affinity IL-2 receptor, including regulatory T cells (Tregs).…”
Section: Il-2 Receptor (Il-2r)mentioning
confidence: 96%
“…Studies carried out in the Ghanaian cohort, in which genotype frequencies of variants of the genes IL-4, IL-13, IL-4R, IL-13RA1 and IL-13RA2 were assigned to the size and number of cavities in patients with TB, showed that some variants of IL-4RA and IL-13RA2 are associated with greater risk of cavity development or progression, pointing to a role for both IL-4Rα and the IL-13Rα2 in the pathogenesis and progression of TB [56]. Experiments with the use of mice with IL-13 overexpression (IL-13tg) and with the absence of IL-4Rα (IL-4Rα−/−) revealed that deletion of IL-4Rα abrogates the increased susceptibility of Mtb-infected IL-13tg mice and the mandatory role for IL-4Rα in mediating the progression dependent on IL-13 of experimental TB [51]. IL-13 overexpression was found to result in recrudescence of Mtb growth accompanied by centrally necrotizing granulomas.…”
Section: Il-4 Receptor (Il-4r)mentioning
confidence: 99%